(untitled) - Amro A.K Gazawi, Ahmad Albloush, Sadi Taha, Majid Kindi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Ball milling is used to produce Al-4wt. %Cu- (2.5-10) vol. % SiC nanocomposites, in which Al, Cu and nano-powder SiC used to produce the nano-powder. The produced nanopowder was consolidated by using powder compact extrusion process. The characterization of the produced bars was done by using tensile testing and electron microscopy. The ultimate tensile strength and hardness was enhanced significantly from 104HV and 168MPa to 153HV and 400 MPA when SiC nanoparticles volume fraction increased to 5% from 2.5%. On other hand, due to the agglomerate of the SiC nanoparticles the ductility decreased from 6.8% to 2%.